Multilevel Contours on Complex Planes - Arni S.R. Srinivasa Rao, (SCHOOL SCIENCE, 2025)
In this article, a new concept called multilevel contours on complex planes that was developed in 2021, is explained to senior high school students who are aware of the basics of real number systems and random variables. These ideas strengthen information geometry principles